EDUKASI DAN PENYULUHAN DAGUSIBU (DAPATKAN, GUNAKAN, SIMPAN, DAN BUANG OBAT DENGAN BENAR) PADA ORANG TUA MAHASISWA DIII TEKNOLOGI LABORATORIUM MEDIK - Dewi Yudiana Shinta; Dyna Putri Mayaserli; Gisky Andria Putra (JURNAL ABDI MERCUSUAR, 2022)
Various health problems, especially those related to medicine, are still encountered in the community. Various problems related to drugs can be caused by people who do not understand the use and handling of drugs properly. One way of managing drugs that is good and correct is by implementing the DAGUSIBU program. The method used in this activity is problem recognition, implementation of DAGUSIBU socialization by means of counseling, interactive discussion. This can support the realization of government programs in improving health services for the community. This socialization increases the participants' understanding of correct drug management. It is hoped that participants will be able to apply the knowledge they have acquired in the family and community environment. DAGUSIBU is a Drug Awareness Family Movement Program initiated by the Indonesian Pharmacists Association in achieving public understanding and awareness of the correct use of drugs (PP IAI, 2014). DAGUSIBU is one of the efforts to improve health for the community which is carried out through health service activities by pharmaceutical personnel. One way of managing drugs that is good and right is by implementing the DAGUSIBU program. This method describes the procedures for drug management from the start of obtaining the drug until the time the drug is no longer consumed and finally discarded. With the various considerations above, the community needs to know the importance of drug management, from getting a prescription to disposing of it if it is not needed. Thus, the impact of misuse of drugs by society can be prevented.